The kaleidoscopic city : Hong Kong, mission, and the evolution of global Pentecostalism - Mayfield, Alex R., 1989- (Baylor University Press, 2023)
"A thematic examination of Pentecostalism in Hong Kong in the early twentieth century as a test case for the study of modern Chinese Pentecostalism"-- Provided by publisher.
Keywords: Hong Kong (China) -- Church history -- 20th century.; China -- Church history -- 20th century.; Pentecostalism -- China -- Hong Kong -- 20th century.; Pentecostalism -- History.; China -- Church history.; Mouvement charismatique -- Histoire.; Chine -- Histoire religieuse.; Mouvement charismatique -- Chine -- Hongkong -- Histoire.; Chine -- Histoire religieuse -- 20e siècle.; Mouvement charismatique -- Chine -- Hongkong -- 20e siècle.; Pentecostalism; China -- Hong Kong; Church history; History